Effectiveness Of Early Mobilization In Restoring Physical Function And Preventing Immobilization In Postoperative Coronary Artery Bypass Graft (Cabg) - Wisnu Guntur Prakoso; Tadi Tadi; Navy Sealsi Adinda Prisca Marina; Abu Bakar (Universitas Pahlawan Tuanku Tambusai, 2025)
The Coronary Artery Bypass Graft (CABG) procedure involves surgical trauma that triggers an inflammatory response, pain, and muscle weakness, so the patient tends to restrict movement. Physiologically, immobilization also reduces blood circulation, increases the risk of thrombosis, and worsens lung function due to lack of early mobilization. This study aims to systematically expose the effect of early mobilization on the recovery of physical function and prevention of immobilization in postoperative coronary artery bypass graft (CABG). The method uses search through 4 main databases, namely PubMed, Scopus, Sciencedirect and ProQuest with a span of 5 years from 2020 to 2025. The literature search used keywords, namely